Influence of calcium sources on the bio-mineralization behavior of Shewanella putrefaciens and induced microbiologically influenced corrosion inhibition - Lou, Yuntian; Zhang, Hao; Chang, Weiwei; Yang, Jingzhi; Chen, Xudong; Hao, Xiangping; Qian, Hongchang; Zhang, Dawei (Frontiers in Microbiology, 2025)
The influence of different calcium sources on the mineralization behavior of Shewanella putrefaciens and their roles in microbiologically influenced corrosion inhibition (MICI) of Q235 carbon steel were investigated. Calcium lactate, calcium nitrate, and calcium L-aspartate were selected as alternative calcium sources to assess their effects on bacterial growth, carbonate deposition, and corrosion resistance. S. putrefaciens exhibited stable growth in all tested media, with the pH exceeding 8 after 14 days, promoting carbonate precipitation. Under sterile conditions, all calcium sources provided some corrosion inhibition, with calcium L-aspartate demonstrating the most effective protection. In bacterial inoculated systems, calcium lactate and calcium L-aspartate facilitated the formation of a continuous CaCO3 mineralized layer, significantly reducing corrosion, whereas calcium nitrate resulted in discontinuous carbonate deposits, promoting localized corrosion. Electrochemical impedance spectroscopy and potentiodynamic polarization analyses confirmed that the mineralized layers formed with calcium lactate and calcium L-aspartate significantly enhanced corrosion resistance, while calcium nitrate exacerbated corrosion due to nitrate-reducing bacterial activity. These findings emphasize the crucial role of calcium source selection in MICI and provide insights for optimizing microbial mineralization strategies for corrosion mitigation.